Implementasi Model Penilaian Hots (Higher Order Thinking Skills) Pada Penilaian Empat Keterampilan Berbahasa Arab - Haniefa, Rifda (Ta'limi | Journal of Arabic Education and Arabic Studies, 2022)
One of the objectives of learning Arabic is to master four Arabic skills :  listening skills, speaking skills, reading skills, and writing skills. The HOTS assessment onOne of the objectives of learning Arabic is to master four Arabic skills :  listening skills, speaking skills, reading skills, and writing skills. The HOTS assessment on four skills aims to make students achieve various competencies that are in accordance with current developments. These competencies are critical thinking, creative and innovative, communication skills, collaboration and confidence. The five things that were conveyed by the government that became the target of the character of students were attached to the evaluation system and were 21st century skills. This research is a qualitative study that produces descriptive data. The type of this research is library research. The data analysis used is content analysis. HOTS assessment on four Arabic language skills can be implemented by aligning the form of assessment and the dimensions of the HOTS thinking process : creating, evaluating and analyzing which are then specified on indicators of competency achievement which are the elaboration of basic competencies four skills aims to make students achieve various competencies that are in accordance with current developments. These competencies are critical thinking, creative and innovative, communication skills, collaboration and confidence. The five things that were conveyed by the government that became the target of the character of students were attached to the evaluation system and were 21st century skills. This research is a qualitative study that produces descriptive data. The type of this research is library research. The data analysis used is content analysis. HOTS assessment on four Arabic language skills can be implemented by aligning the form of assessment and the dimensions of the HOTS thinking process : creating, evaluating and analyzing which are then specified on indicators of competency achievement which are the elaboration of basic competencies.